Benin - Faster and Lower-cost Community Development - Mohan, P.C. (World Bank, Washington, DC, 2012)
The World Bank-assisted Borgou regional pilot rural support project was designed as part of the participatory management approach. It originally involved 250 villages of Benin's Borgou region participating to the Village Level Participatory Approach (VLPA) with the objective of bringing to the local and stakeholder level the design of local development plans and activities. It was implemented by the government and communities from March 1999 through June 2002 at a cost of US$5.06 million, it illustrated how transferring responsibility to communities can reduce costs and increase the pace of rural development.